Clinical analysis of the MyoSure hysteroscopic tissue removal system of endometrial polyps in women with an intact hymen - Jiahui Yong; Xiaohui Guo; Hua Lan; Jing Yuan; Da Zeng; Xiangyang Zeng; Shuijing Yi; Songshu Xiao (BMC, 2021)
Abstract Background To investigate the clinical efficacy of the MyoSure hysteroscopic tissue removal system in the treatment of endometrial and cervical polyps in women with an intact hymen. Methods Retrospective analysis was performed on the clinical data of 32 patients treated with the MyoSure hysteroscopic tissue removal system for endometrial and cervical polyps. Results All the patients successfully completed the procedure. No intraoperative complications, such as cervical trauma, uterine perforation or TURP syndrome, were reported. The surgical time ranged from 5 to 35 min, with an average time of 19.3 min, and the intraoperative blood loss ranged from 2 to 50 ml with an average blood loss of 10.8 ml. After surgery, all patients were shown to have intact hymens. No residual polyp tissues were observed under the microscope, and abnormal uterine bleeding was relieved. Conclusions The MyoSure hysteroscopic tissue removal system can be a safe and effective treatment for endometrial and cervical polyps in women with an intact hymen.